Social anxiety test CASE-A30: Analysis of its psychometric properties - De la Piedra French, Ana Maria Blanca (2023)
The study aims to analyze the psychometric properties of the CASO-A30 Social Anxiety Test by Caballo, Salazar, Irurtia, Arias and the CISO-A Research Team in Peruvian university students. From the sample made up of 350 students from a university in Lima through simple random sampling, with a significance level of 0.05 and a population made up of 1185 students, of both sexes, in 2018 II. Made up of 257 women and 93 men, aged between 18 and 33 years.When evaluating the reliability of the social anxiety questionnaire for adults, a Crobach's Alpha of 0.94 was obtained and ordinal Alpha of 0.95, finding a very high internal consistency (95%), additionally a confirmatory factor analysis of Social Anxiety was performed using the Free Scale Least Squares estimation method, obtaining a GFI of 0.98, AGFI 0.97, NFI 0.97, RFI 0.97 and RMSR 0.08. , confirming that the internal structure presents five dimensions, finally the research confirmed the validity and reliability of the CAS0-A30 Social Anxiety test to identify the attributions in university students of erroneous interpretations of feelings, intentions and behaviors, in which the presence is suggested. of adaptive and maladaptive attributional patterns.